Mixed Plastic Polypropylene Blends
By optimizing the composition of the polypropylene blend, the problems of benzene residue, color inconsistency and uniformity in the recycled polypropylene are solved, and higher surface performance and uniformity are achieved, which is suitable for applications in packaging and medical fields.
Patent Information
- Application Number
- CN202280023137.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-04
- Filing Date
- 2022-03-25
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-03-25
AI Technical Summary
There are problems of benzene residue contamination, color inconsistency and uniformity in existing recirculated polypropylene blends, which limit their application in medical packaging and food packaging.
The contents of crystalline and soluble fractions were determined by CRYSTEX QC analysis, and combined with 13C-NMR spectroscopy and FT-IR spectroscopy, the composition of the polypropylene blend was optimized to ensure its crystalline fractions of 86.0-94.0 wt% and 6.0-14.0 wt% soluble fraction, propylene content in 95.0-99.0 wt% and ethylene content in 1.0-5.0 wt% without benzene detection limit above 80°C, and has a specific color space and large amplitude Oscillation shear-nonlinear factor.
Achieve higher surface properties and uniformity, suitable for demanding end applications, especially in packaging and medical fields, improving the quality and processing properties of recycled materials for polypropylene blends.
Smart Images

Figure CN117083337B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to mixed plastic polypropylene blends, typically from recycled materials. Background Art
[0002] Many attempts have been made to purify recycling streams from post-consumer waste. Among them are washing, screening, aeration, distillation and other measures. For example, WO2018046578 discloses a process for preparing polyolefin recycling materials from mixed color polyolefin waste (including packaging waste), which comprises: first washing the waste with water, then washing it with an alkaline medium at 60°C, and finally sorting the color fragments to obtain color-sorted (white, transparent, other colors) fractions rich in single polyolefins. These fractions are then treated at 50-155°C. US5767230A describes a process comprising contacting a PCR polyolefin chip containing volatile impurities with a heated gas at a superficial velocity sufficient to significantly reduce the volatile impurities (such as odor-active substances). However, contamination with benzene residues has been a problem so far. The source of benzene residues in post-consumer recycling materials remains uncertain, but it has formed an obstacle to final use in fields such as medical packaging and food packaging. Residual (i.e. trace) amounts of benzene are a particularly thorny problem, since odor testing by olfactory testing is not possible. Therefore, end uses that have certain odor requirements are hindered. Color remains an issue that has not been fully resolved. Many recycling applications require the color of the material to be close to what is commonly known as white. Another problem is that known recyclates have certain uniformity problems (reflected by surface contamination of injection molded products). There are special needs for recyclates suitable for injection molding, such as dosing bottle caps, cosmetics, screw caps, caps and closures.
[0003] Therefore, the problem of providing more valuable polypropylene blends remains. Summary of the invention
[0004] The present invention provides a mixed plastic polypropylene blend having
[0005] (i) a crystalline fraction (CF) content of 86.0-94.0 wt% as determined by CRYSTEX QC analysis, and
[0006] (ii) a soluble fraction (SF) content of 6.0-14.0 wt % as determined by CRYSTEX QC analysis, wherein
[0007] (iii) the crystalline fraction (CF) is quantitatively 13 The propylene content (C3(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy is 95.0-99.0 wt%; preferably 96.0-98.0 wt%
[0008] (iv) the crystalline fraction (CF) is quantitatively 13 The ethylene content (C2(CF)) determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy is 1.0-5.0 wt%, preferably 2.0-4.0 wt%, more preferably 2.5-3.5 wt%;
[0009] (v) the intrinsic viscosity (iV(SF)) of the soluble fraction (SF) is from 1.10 to less than 1.50 dl / g, preferably from 1.25 to 1.45 dl / g;
[0010] in
[0011] (vi) the mixed plastic polypropylene blend has an inorganic residue of 0.05-3.0 wt%, preferably 0.05-2.5 wt%, optionally 1.0-2.5 wt%, relative to the mixed plastic polypropylene blend, as measured by calcination analysis (TGA) according to DIN ISO 1172:1996;
[0012] (vii) The mixed plastic polypropylene blend does not contain benzene above the detection limit of HS GC-MS 80°C / 2h;
[0013] (viii) The mixed plastic polypropylene blend has a CIELAB color space (L*a*b*), where
[0014] - L* is 72.0 to 97.0, preferably 80.0 to 97.0;
[0015] -a* is -5.0 to 0.0;
[0016] - b* is 0.0 to less than 22.0; and
[0017] in
[0018] (ix) The large amplitude oscillatory shear-nonlinear factor [LAOS-NLF] (190°C, 1000%) of the mixed plastic polypropylene blend is greater than 2.3, wherein
[0019]
[0020] In the formula
[0021] G1' is the first-order Fourier coefficient
[0022] G3' is the third-order Fourier coefficient.
[0023] The present invention also relates to a granular mixed plastic polypropylene blend and a peroxide visbroken mixed plastic polypropylene blend. The present invention also provides articles made from the mixed plastic polypropylene blend and uses in packaging and / or medical fields. In another aspect, the present invention relates to a blend of the mixed plastic polypropylene blend with at least one virgin olefin.
[0024] Mixed plastics are defined as the presence of small amounts of compounds not normally present in virgin propylene blends, such as polystyrene, polyamides, polyesters, wood, paper, limonene, aldehydes, ketones, fatty acids, metals and / or long term decomposition products of stabilizers. Virgin propylene blends are blends that originate directly from the production process without intermediate use.
[0025] By definition, "mixed plastics" may be equated to detectable amounts of polystyrene and / or polyamide-6 and / or limonene and / or fatty acids.
[0026] The mixed plastic polypropylene blend has a further broadened molecular weight distribution because it is a mechanical blend of countless polypropylene and very small amounts of low density polyethylene and linear low density polyethylene. Those skilled in the art will appreciate that polypropylene from a variety of producers will eventually enter the plastic waste stream, especially when pre-sorted in a polyolefin-rich plastic waste stream.
[0027] Furthermore, the skilled person will also appreciate that a soluble fraction (SF) obtained by CRYSTEX QC analysis having an intrinsic viscosity (iV(SF)) of 1.10 to less than 1.50 dl / g is typically present in material from a recycle stream. In a preferred aspect of the invention, the soluble fraction (SF) obtained by CRYSTEX QC analysis has an intrinsic viscosity (iV(SF)) of 1.25 to less than 1.45 dl / g.
[0028] Surprisingly it has been found that the mixed plastic polypropylene blend according to the present invention provides improved surface properties, enabling many demanding end-use applications.
[0029] In a first embodiment, the amounts of the crystalline fraction (CF) and the soluble fraction (SF) analyzed by CRYSTEX QC are preferably:
[0030] The crystalline fraction (CF) content is 87.0 to 90.0 wt%,
[0031] The soluble fraction (SF) content is 10.0 to 13.0 wt%.
[0032] In a second embodiment, the amounts of crystalline fraction (CF) and soluble fraction (SF) analyzed by CRYSTEX QC are:
[0033] The crystalline fraction (CF) content is 91.0 to 94.0 wt%,
[0034] The soluble fraction (SF) content is 6.0 to 9.0 wt%.
[0035] In a first embodiment, the mixed plastic polypropylene blend has a CIELAB color space (L*a*b*) where:
[0036] - L* is 85.0 to 97.0;
[0037] -a* is -5.0 to 0.0;
[0038] -b* is 0.0 to less than 8.0.
[0039] In a second embodiment, the mixed plastic polypropylene blend has a CIELAB color space (L*a*b*) where
[0040] - L* is 72.0 to 97.0, preferably 80.0 to 97.0;
[0041] -a* is -5.0 to 0.0;
[0042] - b* is 0.0 to below 22.0, typically above 8.0 to below 22.0.
[0043] The color of CIELAB will be affected by the sorting process. The more yellowish the material is, the higher the b* value will be.
[0044] The melt flow rate (ISO1133, 2.16 kg; 230°C) of the mixed plastic polypropylene blend according to the present invention is typically 2.0 to 100 g / 10 min. The melt flow rate can be influenced by splitting post-consumer plastic waste streams, for example but not limited to: from producer responsibility extension programs (such as DSD in Germany), or sorting out a large number of pre-sorted fractions from municipal solid waste and remixing them in an appropriate manner. As another way to change the melt flow rate of the final mixed plastic polypropylene mixture, peroxides can be introduced in the final granulation step. Typically, the melt flow rate is 2.0 to 100 g / 10 min, preferably 5.0 to 80 g / 10 min, more preferably 10 to 60 g / 10 min, and most preferably 12 to 55 g / 10 min.
[0045] The preferred range of MFR of the second embodiment is 2.0 to 12 g / 10 min (ISO 1133, 2.16 kg; 230° C.). This MFR range is particularly suitable for non-visbroken mixed plastic polypropylene blends. By visbreaking, the MFR of the second embodiment can also be increased to 30 g / 10 min.
[0046] Typically the polypropylene mixed plastic according to the invention will be a recycled material.
[0047] Typically, recycling properties can be assessed by the presence of one or more of the following:
[0048] a) Polystyrene
[0049] b) Polyamide-6
[0050] c) Limonene determined by solid phase microextraction (HS-SPME-GC-MS)
[0051] d) Fatty acids determined by solid phase microextraction (HS-SPME-GC-MS).
[0052] The presence refers to the detection limit. The detection limit of limonene and fatty acids by solid phase microextraction (HS-SPME-GC-MS) is less than 0.1 ppm, ie, the trace amounts of these substances make it easy to judge the recycling nature.
[0053] The preferred amounts are as follows
[0054] a) Polystyrene: 0-2.0 wt%; more preferably 0 to 0.5 wt%
[0055] b) Polyamide-6: 0 to 1.5 wt%; more preferably 0 to 0.5 wt%
[0056] c) Limonene determined by solid phase microextraction (HS-SPME-GC-MS): 0.1 ppm to 50 ppm
[0057] d) Fatty acids determined by solid phase microextraction (HS-SPME-GC-MS): 0.1 ppm to 200 ppm, more preferably 50 ppm.
[0058] It goes without saying that the amounts of a), b), c) and d) should be as low as possible. In a particularly preferred embodiment, the mixed plastic polypropylene blend contains neither polystyrene nor polyamide, which means that both polymers are below the detection limit.
[0059] According to the present invention, preferably, the ethylene content (C2(SF)) of the soluble fraction (SF) obtained by CRYSTEX QC analysis of the mixed plastic polypropylene mixture is 12.0 to 32.0 wt%, and the ethylene content (C2(SF)) is determined by quantitative 13 FT-IR spectroscopy calibrated by C-NMR spectroscopy.
[0060] In a first embodiment, preferably, the ethylene content (C2(SF)) of the soluble fraction (SF) obtained by CRYSTEXQC analysis of the mixed plastic polypropylene blend according to the present invention is 25.0 to 32.0 wt%, and the ethylene content (C2(SF)) is determined by quantitative 13 FT-IR spectroscopy calibrated by C-NMR spectroscopy.
[0061] In a second embodiment, preferably, the ethylene content (C2 (SF)) of the soluble fraction (SF) obtained by CRYSTEXQC analysis of the mixed plastic polypropylene blend according to the present invention is 10.0 to 25.0 wt%, more preferably 12.0 to 25.0 wt%, still more preferably 12.0 to 20.0 wt%, most preferably 14.0 to 19.0 wt%, and the ethylene content (C2 (SF)) is obtained by quantitative 13 FT-IR spectroscopy calibrated by C-NMR spectroscopy.
[0062] Preferably, the odor (VDA270-B3) of the mixed plastic polypropylene blend according to the present invention is preferably below 4.0, more preferably below 3.0. It should be understood that many commercial recycling grades that do not report odor are actually worse due to the presence of problematic substances prohibiting odor detection according to VDA270.
[0063] On the other hand, the mixed plastic polypropylene blend according to the present invention, in particular the first embodiment, has a large amplitude oscillatory shear-nonlinear factor (LAOS-NLF) (190° C.; 1000%) preferably higher than 2.7, more preferably higher than 3.3, wherein
[0064]
[0065] In the formula
[0066] G1' is the first-order Fourier coefficient
[0067] G3' is the third-order Fourier coefficient
[0068] In the second embodiment, the large amplitude oscillatory shear-nonlinear factor (LAOS-NLF) (190° C.; 1000%) is only higher than 2.3.
[0069] Without wishing to be bound by theory, it is believed that the processing of the polymers causes branching initiated by the accompanying contaminants. The choice of raw materials may affect the LAOS-NLF so that about 10 wt% of the material is soft polypropylene. Here, "soft polypropylene" means a tensile modulus (measured as described in the experimental section) below 900 MPa. The addition of low density polyethylene and linear low density polyethylene, more precisely, a low crystalline PE fraction (LCF-PE) present in an amount of 2.0 to 4.0 wt% (observed in the CFC analysis), also causes a large amplitude oscillatory shear-nonlinear factor (LAOS-NLF) (190°C; 1000%) above 2.3. It should be understood that some regions operate collection stations that collect post-consumer pre-sorted plastics. This high value plastic stream is commercially available and can upgrade other low quality plastic streams from other waste processing resources (for example, through softer polypropylene blends). The second embodiment with a higher crystalline fraction (CF) (i.e., a crystalline fraction (CF) content of 91.0 to 94.0 wt% and a soluble fraction (SF) content of 6.0 to 9.0 wt%) is more restricted, wherein the large amplitude oscillatory shear non-linear factor (LAOS-NLF) (190°C; 1000%) is slightly lower.
[0070] On the other hand, the mixed plastic polypropylene blend according to the first embodiment of the present invention has a tensile modulus (ISO 527-2, cross head speed of 1 mm / min; 23°C) of at least 1300 MPa, preferably at least 1350 MPa, and most preferably at least 1390 MPa, measured using injection molded test specimens (dog bone shape, 4 mm thickness) as described in EN ISO 1873-2. This relatively high tensile modulus is due to the relatively small amount of rubber-like and plastic-like materials. Typically, the tensile modulus (ISO 527-2, cross head speed of 1 mm / min; 23°C) of the first embodiment is not higher than 1500 MPa.
[0071] The mixed plastic polypropylene mixture according to the second embodiment of the present invention has a tensile modulus (ISO 527-2, crosshead speed of 1 mm / min; 23° C.) of at least 1200 MPa, preferably at least 1250 MPa, measured using an injection molded test specimen (dog bone shape, 4 mm thick) as described in EN ISO 1873-2. Typically, the tensile modulus (ISO 527-2, crosshead speed of 1 mm / min; 23° C.) of the second embodiment is not higher than 1400 MPa.
[0072] The mixed plastic polypropylene blend according to the first embodiment of the present invention unexpectedly has a special time stability for melt flow rate, eta (2.7 kPa) and eta (300 rad / s). An unexpected advantage, namely an unusually high melt strength, was also observed. Further unexpectedly, the mixed plastic polypropylene blend according to the present invention has an unusually good uniformity. For example, when analyzed separately, the melt flow rate, eta (2.7 kPa) and eta (300 rad / s) of different (selected) pellets of the same batch show substantially the same values. This is a special discovery because it is expected that the recycled material will have a substantial change.
[0073] The mixed plastic polypropylene blend produced according to the second embodiment has excellent processing properties (reflected by the shear thinning factor), with a shear thinning factor (STF) (which is the ratio of eta0.05 and eta300) higher than 13.0.
[0074] The Charpy notched impact strength (non-instrumented, ISO 179-1, +23°C) of the mixed plastic polypropylene blend according to the present invention is preferably higher than 4.0 kJ / m 2 , more preferably higher than 4.5 kJ / m 2 The Charpy notched impact strength (non-instrumented, ISO 179-1, +23°C) of the mixed plastic polypropylene blend according to the second embodiment is preferably higher than 6.0 kJ / m 2 , more preferably higher than 8.0 kJ / m 2 , most preferably above 8.3 kJ / m 2 .
[0075] In a particularly preferred embodiment, the mixed plastic polypropylene blend according to the invention has a Charpy notched impact strength (NIS) (1eA) (non-instrumented, ISO 179-1, +23° C.) of at least 8.0 kJ / m at +23° C. on an injection molded specimen of 80×10×4 mm prepared according to EN ISO 1873-2 according to ISO 179-1eA. 2 , preferably 8.3 kJ / m 2 , wherein further, the ethylene content (C2(SF)) of the soluble fraction (SF) obtained by CRYSTEX QC analysis is 12.0-20.0 wt%, and the ethylene content (C2(SF)) is determined by quantitative 13 Further preferably, the mixed plastic polypropylene blend has a CIELAB color space (L*a*b) as determined by FT-IR spectroscopy calibrated by C-NMR spectroscopy, wherein:
[0076] - L* is 72.0 to 97.0, preferably 80.0 to 97.0;
[0077] -a* is -5.0 to 0.0;
[0078] -b* is 0.0 to less than 22.0
[0079] In particularly preferred aspects of the second embodiment, the crystalline fraction (CF) content determined according to CRYSTEX QC analysis is preferably 91.0 to 94.0 wt%, and the soluble fraction (SF) content determined according to CRYSTEX QC analysis is preferably 6.0 to 9.0 wt%.
[0080] The mixed plastic polypropylene blend according to the present invention, ie the first embodiment and the second embodiment, is preferably in the form of pellets. Pelletization can reduce the content of volatile substances.
[0081] In one embodiment, the mixed plastic polypropylene blend according to the present invention is visbroken by one or more peroxides. The mixed plastic polypropylene blend can be subjected to visbreaking like any other original polypropylene blend. If the mixed plastic polypropylene blend according to the present invention is subjected to visbreaking, decomposition products of the visbreaking process may be present in the resulting blend. It should be understood that the decomposition products of the visbreaking process (such as the original materials conventionally used in the art) are not considered to be impurities. The first embodiment and the second embodiment can be visbroken.
[0082] In another aspect, the present invention relates to a molded article made from the mixed plastic polypropylene blend described herein. This applies to the first and second embodiments.
[0083] In yet another aspect, the present invention relates to a blend containing the mixed plastic polypropylene blend described herein and at least one virgin polyolefin. This applies equally to the first and second embodiments. For example, the virgin propylene homopolymer contained in the heterophasic polypropylene can be replaced by the mixed plastic polypropylene blend described herein.
[0084] The present invention also relates to the use of the mixed plastic polypropylene blend according to the present invention, ie the first embodiment and the second embodiment, in the packaging sector and / or in the medical sector. DETAILED DESCRIPTION
[0085] The process of providing the mixed plastic polypropylene blend according to the present invention is highly challenging. The process comprises the following steps:
[0086] a) Provide post-consumer plastic waste;
[0087] b) Sorting of commodities made from polystyrene, polyamide, polyethylene, metal, paper, wood and other non-polypropylene materials, thus providing post-consumer plastic materials;
[0088] c) sorting colored goods to provide post-consumer plastic materials, wherein the post-consumer plastic materials include mainly white bottles, mainly white yogurt cups, mainly white cans, mainly colorless panels, mainly colorless parts, etc.;
[0089] d) selected predominantly white or colorless post-consumer plastic materials are ground, washed in aqueous solution with various detergents, and then dried, windsifted, and screened;
[0090] e) further sorting the pre-treated post-consumer plastic material to eliminate non-polyolefin and colored components to obtain an intermediate;
[0091] f) a quality control step in which the intermediate of step e) is subjected to cross-fractionation chromatography, the low crystalline polyethylene fraction (LCF-PE) is determined in CFC and again checked whether this amount is within the range of 2.0 to 4.0 wt%;
[0092] g) discarding the intermediate having a low crystalline polyethylene fraction not in the range of 2.8 to 4.2 wt %;
[0093] h) extruding said material to obtain the polypropylene blend according to the present invention in the form of pellets;
[0094] i) Optional aeration, which is performed by preheating the post-consumer plastic material to a temperature of preferably 100-130°C using a gas stream having a temperature of at least 100°C.
[0095] A variety of possible raw materials are available from separate collection systems (such as extended producer responsibility programs), as well as specific municipal waste collection systems, to provide post-consumer plastic waste. The purity of these raw materials will vary, depending on the level of consumer involvement and the quality of the relevant sorting equipment, which is usually determined by the collection system. After step b), the intermediates can also be screened to determine whether there are obviously very old ("ancient") mainly colorless / natural plastic products. Discoloration (such as obvious yellowing) and / or obvious scratches on mainly colorless / natural plastic products can be sorted. This step can remove the so-called substances of very high concern. These substances (such as lead, mercury, polybrominated diphenyl ethers, etc.) have been banned for a long time, but they still exist in the real world because consumers tend to hoard plastic products (such as plastic toys) for many years and eventually discard them into the collection system. The additional screening step can be assisted by analytical control of the substances of very high concern.
[0096] There are many methods for odor control and evaluation. An overview is provided here and is incorporated herein by reference, for example, Demets, Ruben et al. "Development and application of odor quantification analysis methods in plastic waste recycling processes." Resources, Conservation and Recycling 161 (2020): 104907.
[0097] experiment
[0098] The following examples are included to demonstrate specific aspects and embodiments of the invention described in the claims. However, those skilled in the art should appreciate that the following description is illustrative only and should not be viewed in any way as limiting the invention.
[0099] Test Method
[0100] a) CRYSTEX
[0101] Determination of the crystalline and soluble fractions and their properties (IV and ethylene content)
[0102] The crystalline (CF) fraction and the soluble (SF) fraction of the polypropylene (PP) composition were analyzed using a CRYSTEX instrument (Polymer Char, Valencia, Spain), as well as the comonomer content and intrinsic viscosity of the respective fractions. Details of the technique and methods can be found in the literature (Ljiljana Jeremic, Andreas Albrecht, Martina Sandholzer & Markus Gahleitner (2020) Rapid characterization of high impact ethylene-polypropylene copolymer compositions by crystallization extraction separation: comparability with standard separation methods, International Journal of Polymer Analysis and Characterization, 25: 8, 581-596)
[0103] The crystalline and amorphous fractions were separated by the following temperature cycle: dissolution in 1,2,4-trichlorobenzene at 160°C, crystallization at 40°C, and redissolution in 1,2,4-trichlorobenzene. SF and CF were quantified by an integrated infrared detector (IR4) and the ethylene content (C2) was determined, and the intrinsic viscosity (IV) was determined using an online double capillary viscometer.
[0104] The IR4 detector is a multi-wavelength detector that measures two different bands (CH3 stretching vibration (centered at about 2960 cm -1 ) and CH stretching vibration (2700-3000cm -1)) infrared absorption. The IR4 detector is used with a series of 8 known ethylene contents ranging from 2 wt% to 69 wt% (given by 13 C-NMR measurement) was calibrated with EP copolymers, each copolymer having a variety of concentrations from 2 to 13 mg / ml. In order to simultaneously meet the expected characteristics of various polymer concentrations (concentration and ethylene content), the following calibration equation was applied during Crystex analysis:
[0105] Concentration = a + b * Abs(CH) + c * (Abs(CH)) 2 +d*Abs(CH3)+e*(Abs(CH3) 2 +f*Abs(CH)*Abs(CH3) (Formula 1)
[0106] CH3 / 1000C=a+b*Abs(CH)+c*Abs(CH3)+d*(Abs(CH3) / Abs(CH))+e*(Abs(CH3) / Abs(CH)) 2 (Formula 2)
[0107] Constants a to e of Formula 1 and constants a to f of Formula 2 are determined by least squares regression analysis.
[0108] The CH3 / 1000C is converted to ethylene content (in wt%) using the following relationship:
[0109] Wt% (ethylene in EP copolymer) = 100-CH3 / 1000TC*0.3 (Formula 3)
[0110] The amounts of the soluble fraction (SF) and the crystalline fraction (CF) are related to the amount of the xylene cold soluble fraction (XCS) and the amount of the xylene cold insoluble fraction (XCI) (determined by the standard gravimetric method according to ISO 16152) by means of the XS calibration. The XS calibration was achieved by testing a number of EP copolymers with an XS content in the range of 2-31 wt%. The determined XS calibration is linear:
[0111] Wt%XS=1.01*Wt%SF (Formula 4)
[0112] The intrinsic viscosity (IV) of the parent EP copolymer and its soluble and crystalline fractions was determined using an online double capillary viscometer and correlated to the corresponding IV (determined according to the standard method of ISO 1628-3 in decalin). Calibration was performed with various EP PP copolymers with IV = 2-4 dL / g. The calibration curve determined was linear:
[0113] IV(dL / g)=a*Vsp / c (Formula 5)
[0114] The samples to be analyzed were weighed at a concentration of 10 mg / ml to 20 mg / ml. To avoid injection of possible gels and / or polymers (such as PET and PA) not soluble in TCB at 160°C, the weighed samples were packed in MW 0,077 / D 0,05 mm stainless steel meshes.
[0115] After automatically filling the vial with 1,2,4-TCB (as antioxidant) containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT), the sample was dissolved at 160°C and stirred continuously at 400 rpm until completely dissolved, usually for 60 minutes. To avoid sample degradation, the polymer solution was covered with a nitrogen atmosphere during the dissolution process.
[0116] A certain volume of sample solution is injected into a column filled with an inert carrier, where the sample is crystallized and the soluble fraction is separated from the crystalline fraction. This process is repeated twice. In the first injection, the entire sample is measured at high temperature, and the IV [dl / g] and C2 [wt%] of the PP composition are determined. In the second injection, the soluble fraction (low temperature) and the crystalline fraction (high temperature) of the crystallization cycle are measured (Wt% SF, Wt% C2, IV).
[0117] b) NMR spectroscopy to quantify microstructure (calibration only)
[0118] Calibration was performed using quantitative nuclear magnetic resonance (NMR) spectroscopy.
[0119] Quantitative 13C{1H}NMR spectra were recorded in solution using a Bruker Avance Neo 400 NMR spectrometer, operating at 400.15 and 100.62 MHz for 1H and 13C, respectively. All spectra were recorded at 125°C using a 13C optimized 10 mm extended temperature probe, and nitrogen was used for all atmospheres. Approximately 200 mg of material was dissolved in approximately 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) and approximately 3 mg of BHT (2,6-di-tert-butyl-4-methylphenol CAS 128-37-0) and chromium-(III)-acetylacetone (Cr(acac)3) to form a 60 mM solution of a relaxation agent as solvent, as described in G. Singh, A. Kothari, V. Gupta, Polymer Testing 2009, 28(5), 475.
[0120] To ensure that the solution is homogeneous, the NMR tube is further heated in a rotating furnace for at least 1 hour after preliminary sample preparation in a heating block. After insertion of the magnet, the NMR tube rotates at a speed of 10 Hz. This setting was chosen mainly due to the quantitative requirements for high resolution and accurate quantification of ethylene content. Standard single pulse excitation without NOE was used, using optimized sharp angles, 1 second cycle delay and dual-level WALTZ16 decoupling schemes, such as Z. Zhou, R. Kuemmerle, X. Qiu, D. Redwine, R. Cong, A. Taha, D. Baugh, B. Winniford, J. Mag. Reson. 187 (2007) 225 and V. Busico, P. Carbonniere, R. Cipullo, C. Pellecchia, J. Severn, G. Talarico, Macromol. Rapid Commun. 2007, 28, 1128. A total of 6144 (6k) transient values were obtained for each spectrum.
[0121] The quantitative 13C{1H}NMR spectra were processed and integrated, and the relevant quantitative properties were determined from the integration. All chemical shifts were indirectly referenced to the central methylene of the ethylene segment (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allows for comparable referencing even if this structural unit is not present.
[0122] Characteristic signals corresponding to ethylene incorporation were observed (as described in Cheng, HN, Macromolecules 1984, 17, 1950) and the comonomer fraction was calculated as the ethylene fraction in the polymer relative to all monomers in the polymer:
[0123] fE=(E / (P+E)
[0124] The comonomer fraction was quantified by integrating multiple signals in the 13C{1H} spectrum across the entire spectral region using the method of WJ. Wang and S. Zhu, Macromolecules, 2000, 33 1157. Minor adjustments to the integration region were made to increase applicability across all ranges involving comonomer content.
[0125] Calculate the mole percentage of added comonomer from the mole fraction:
[0126] E[mol%]=100*fE
[0127] Calculate the weight percentage of added comonomer from the molar fraction:
[0128] E[wt%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08)).
[0129] c) Tensile modulus and tensile strain at break were measured according to ISO 527-2 (crosshead speed = 1 mm / min; test speed 50 mm / min at 23° C.) using injection molded specimens as described in EN ISO 1873-2 (dog bone shape, 4 mm thickness). The measurements were done after 96 hours of conditioning.
[0130] d) Impact strength was determined by measuring the Charpy notched impact strength (1 eA) (non-instrumented, ISO 179-1 at +23° C.) of 80×10×4 mm injection molded specimens (prepared according to EN ISO 1873-2) at +23° C. according to ISO 179-1 eA standard.
[0131] e) Inorganic residues: TGA according to DIN ISO 1172:1996 using a Perkin Elmer TGA 8000. Approximately 10-20 mg of material was placed in a platinum pan. The temperature was equilibrated at 50°C for 10 minutes and then increased to 950°C under nitrogen at a heating rate of 20°C / min. The ash content was evaluated as weight percent at 850°C.
[0132] f) MFR: Melt flow rate measured at 230° C. with a load of 2.16 kg (MFR2). The melt flow rate is the amount of polymer in g which the testing apparatus (standardized to ISO 1133) extrude in 10 minutes at a temperature of 230° C. with a load of 2.16 kg.
[0133] g) Amount of metal
[0134] Determined by X-ray fluorescence (XRF).
[0135] h) Amount of paper and wood (for comparison purposes only)
[0136] Paper and wood can be assayed by conventional laboratory methods including grinding, flotation, microscopic observation and thermogravimetric analysis (TGA).
[0137] i) Benzene content
[0138] The determination was performed using HS GC-MS at 80°C / 2h, as described below.
[0139] Static Headspace Analysis
[0140] The parameters employed for static headspace gas chromatography / mass spectrometry (HS / GC / MS) are described here.
[0141] Weigh 4.000 ± 0.100 g of sample, put it into a 20 ml HS vial, and seal it with a PTFE cap.
[0142] The mass spectrometer was operated in scan mode and the total ion chromatogram (TIC) was recorded for each analysis. More detailed information on applicable method parameters and data evaluation is given below:
[0143] -HS parameters (Agilent G1888 headspace sampler)
[0144] Balancing time in bottle: 120min
[0145] Oven temperature: 80℃
[0146] Circuit temperature: 205℃
[0147] Transportation pipeline temperature: 210℃
[0148] Low vibration
[0149] -GC parameters (Agilent 7890A GC system)
[0150] Chromatographic column: ZB-WAX 7HG-G007-22 (30m×250μm×1μm)
[0151] Carrier gas: Helium 5.0
[0152] Flow rate: 2ml / min
[0153] Split ratio: 5:1
[0154] GC oven program: 35°C, 0.1 min
[0155] 10℃ / min to 250℃
[0156] 250℃,1min
[0157] -MS parameters (Agilent 5975C Inert XL MSD)
[0158] Collection method: Scan
[0159] Scan parameters:
[0160] Low Quality: 20
[0161] High quality: 200
[0162] Threshold: 10
[0163] -Software / data evaluation
[0164] MSD ChemStation E.02.02.1431
[0165] MassHunter GC / MS Acquisition B.07.05.2479
[0166] AMDIS GC / MS Analysis Version 2.71
[0167] NIST Mass Spectral Library Version 2.0g
[0168] -AMDIS Deconvolution Parameters
[0169] Minimum Match Factor: 80
[0170] Threshold: Low
[0171] Scan Direction: High to Low
[0172] Data File Format: Agilent File
[0173] Instrument Type: Quadrupole
[0174] Component Width: 20
[0175] Adjacent Peak Subtraction: 2
[0176] Resolution: High
[0177] Sensitivity: Very High
[0178] Shape Requirement: Medium
[0179] Solvent Tail: 44 m / z
[0180] Column Drain: 207 m / z
[0181] Minimum Model Peaks: 2
[0182] Minimum S / N: 10
[0183] Minimum Specific Peaks: 0.5
[0184] Data Evaluation
[0185] The TIC data was further deconvolved with the assistance of AMDIS software (see the above parameters) and compared with a custom target library based on the mass spectral library (NIST). The corresponding mass spectra of the selected substances (such as benzene) were included in the custom target library. A substance was only accepted as "preliminary identification" when the identified peak showed a minimum match factor of 80 and was confirmed as a match by an experienced mass spectrometrist.
[0186] In this study, "below the detection limit" (<LOD) refers to the situation where the match factor is below 80 (AMDIS) or even the peak cannot be identified. The results only relate to the measured samples, measurement times, and applied parameters.
[0187] j) CIELAB color space (L*a*b*)
[0188] In the CIE L*a*b* uniform color space, the color coordinates measured according to DIN EN ISO 11664-4 are: L* - lightness coordinate; a* - red / green coordinate, +a* for red, -a* for green; b* - yellow / blue coordinate, +b* for yellow, -b* for blue. The L*, a* and b* axes define the three-dimensional CIE color space. Standard Konica / Minolta colorimeter CM-3700A.
[0189] k) Odor VDA270-B3
[0190] VDA 270 is a method for determining the odor characteristics of automotive trim materials. In this study, the odor was determined according to VDA 270 (2018) variant B3. After removing the cap as little as possible, each assessor evaluated the odor of the respective sample according to the VDA 270 scale. The six-point scale consists of the following levels: level 1: not perceptible, level 2: perceptible, not disturbing, level 3: perceptible, but not disturbing, level 4: disturbing, level 5: strongly disturbing, level 6: unacceptable. The assessors remained calm during the assessment and were not allowed to compromise with each other by discussing the individual results during the test. They were also not allowed to adjust their evaluation after testing another sample. For statistical reasons (and accepted by VDA 270), the assessors had to use the full procedure when evaluating. Therefore, the odor level was based on the average of all independent evaluations and was rounded to an integer.
[0191] l) Limonene detection
[0192] Quantification of limonene can be performed by the standard addition method using solid phase microextraction (HS-SPME-GC-MS).
[0193] 50 mg of ground sample was weighed into a 20 mL headspace vial, and after adding different concentrations of limonene and a glass-coated magnetic stir bar, the vial was capped with a silicone / PTFE-lined magnetic cap. The samples were spiked with known concentrations of diluted limonene standards using microcapillaries (10 pL). 0, 2, 20, and 100 ng (equivalent to 0 mg / kg, 0.1 mg / kg, 1 mg / kg, and 5 mg / kg, respectively) of limonene were added, and in addition, limonene standards with contents of 6.6 mg / kg, 11 mg / kg, and 16.5 mg / kg were also used in conjunction with some of the samples tested in this application. For quantification, ion 93 collected in SIM mode was used. Enrichment of the volatile fraction was performed by headspace solid phase microextraction using a 2 cm stable curved 50 / 30 pm DVB / Carboxen / PDMS fiber at 60 °C for 20 min. Desorption was performed directly in the heated injection port of the GCMS system at 270 °C.
[0194] GCMS parameters:
[0195] Chromatographic column: 30m HP 5 MS 0.25*0.25
[0196] Injector: No split, 0.75mm SPME liner, 270℃
[0197] Temperature program: -10℃(1min)
[0198] Carrier gas: Helium 5.0, 31cm / s linear velocity, constant flow
[0199] Mass spectrometry: single quadrupole, direct interface, interface temperature 280°C
[0200] Collection method: SIM scanning mode
[0201] Scan parameters: 20~300amu
[0202] SIM parameters: m / Z93, dwell time 100ms
[0203] m) Fatty acid detection
[0204] Fatty acid quantification can be performed using headspace solid phase microextraction (HS-SPME-GC-MS) by standard addition method.
[0205] 50 mg of ground sample was weighed into a 20 mL headspace vial and the vial was capped with a silicone / PTFE lined magnetic cap after adding different concentrations of limonene and a glass coated magnetic stirring bar. Three concentration levels of known concentrations of undiluted fatty acid mixtures (acetic acid, propionic acid, butyric acid, valeric acid, hexanoic acid and octanoic acid) standards were added to the sample using a 10 μL microcapillary. 0, 50, 100 and 500 ng (equivalent to 0 mg / kg, 1 mg / kg, 2 mg / kg and 10 mg / kg) of each acid were added. For quantification, all acids used ion 60 obtained in SIM mode, except for propionic acid, which used ion 74.
[0206] GCMS parameters:
[0207] Column: 20m ZB wax, 0.25*0.25
[0208] Injector: split ratio 5:1, glass-lined split liner, 250°C
[0209] Temperature program: 40℃ (1min) @6℃ / min to 120℃, @15℃ to 245℃ (5min)
[0210] Carrier gas: Helium 5.0, 40cm / s linear velocity, constant flow
[0211] MS: Single quadrupole, direct interface, interface temperature 220°C
[0212] Collection method: SIM scanning mode
[0213] Scan parameters: 46~250amu 6.6 scans / second
[0214] SIM parameters: m / z 60, 74, 6.6 scans / sec
[0215] n) The presence of polyamide-6 and polystyrene
[0216] Using FTIR spectroscopy, the -1 (PS) and 3300cm -1 (PA6) absorption band.
[0217] o) Determination of contaminants on panels
[0218] The plates were injection molded and had dimensions of 150 x 80 x 2 mm. Five plates were then imaged (photographed) at high resolution (by placing them close to each other). The images were then analyzed by software that automatically counted the number of visual defects (to the naked eye) due to contaminants.
[0219] p) Dynamic shear measurement (Eta (2.7 kPa) and Eta (300 rad / s))
[0220] Characterization of polymer melts by dynamic shear measurements in accordance with ISO standards 6721-1 and 6721-10. The measurements were performed with an Anton Paar MCR501 stress-controlled rotational rheometer equipped with 25 mm parallel plate geometry. The measurements were performed on press-formed plates, using a nitrogen atmosphere and setting the strain in the linear viscoelastic region. The oscillatory shear tests were performed at 230 °C, with an applied frequency range between 0.01 and 600 rad / s and a set gap of 1.3 mm.
[0221] In a dynamic shear experiment, the probe undergoes uniform deformation under sinusoidally varying shear strain or shear stress (strain and stress controlled modes, respectively). In a controlled strain experiment, the probe is subjected to a sinusoidal strain that can be expressed as
[0222] γ(t)=γ0 sin(ωt) (1)
[0223] If the applied strain is in the linear viscoelastic region, the resulting sinusoidal stress response can be expressed as
[0224] σ(t)=σ0 sin(ωt+δ) (2)
[0225] In the formula
[0226] σ0 is the stress amplitude, γ0 is the strain amplitude
[0227] ω is the angular frequency
[0228] δ is the phase shift (loss angle between applied strain and stress response)
[0229] t is time
[0230] Dynamic test results are usually expressed in terms of several different rheological functions, namely shear storage modulus G′, shear loss modulus G″, complex shear modulus G*, complex shear viscosity η*, dynamic shear viscosity η′, complex shear viscosity external component η″ and loss tangent tanδ, which can be expressed as follows:
[0231]
[0232]
[0233] G * =G′+iG″[Pa] (5)
[0234] η * =η′-iη″[Pa.s] (6)
[0235]
[0236]
[0237] ETA (x kPa)) is determined by Equation 9.
[0238] ETA(x kPa)=Eta * For (G * =x kPa)[Pa.s] (9)
[0239] For example, ETA(2.7 kPa) is defined by the complex viscosity value, which is determined by the value of the complex modulus equal to 2.7 kPa.
[0240] ETA (x rad / s) is determined by Equation 10.
[0241] ETA(x rad / s)=Eta * For (ω=x rad / s)[Pa.s] (10)
[0242] For example, ETA(300 rad / s) is defined by the complex viscosity value, which is determined at a frequency sweep of 300 rad / s.
[0243] q) The shear thinning factor (STF) is defined as
[0244]
[0245] These values were determined by a single-point interpolation procedure defined by the Rheoplus software. In case a given G* value was not reached experimentally, it was determined by means of extrapolation using the same procedure as before. In both cases (interpolation or extrapolation), the Rheoplus options "-Interpolate y values to x values from parameters" and "Logarithmic interpolation type" were applied.
[0246] References:
[0247] [1] Rheological characterization of polyethylene fractions” Heino, E.L., Lehtinen, A., Tanner J., J., Neste Oy, Porvoo, Finland, Theor. Appl. Rheol., Proc. Int. Congr. Rheol, 11th (1992), 1, 360-362
[0248] [2] “Effect of polyethylene molecular structure on some rheological properties”, Heino, EL, Borealis Polymers Oy, Porvoo, Finland, Annual Transactions of the Nordic Rheology Society, 1995.).
[0249] [3] Definition of terms related to non-limiting mechanical properties of polymers, Pure & Appl. Chem., Vol. 70, No. 3, pp. 701-754, 1998.
[0250] r) Large Amplitude Oscillatory Shear (LAOS)
[0251] The large amplitude oscillatory shear method is used to study the nonlinear viscoelastic behavior under shear flow. The method requires the application of a sinusoidal strain amplitude γ0 at a given angular frequency ω at a given time t. As long as the applied sinusoidal strain is high enough, a nonlinear response will be generated. In this case, the stress σ is a function of the applied strain amplitude, time and angular frequency. Under these conditions, the nonlinear stress response is still a periodic function; however, it can no longer be represented by a single harmonic sine wave. The stress generated by the nonlinear viscoelastic response [1-3] can be expressed by a Fourier series that includes the contribution of higher harmonics:
[0252] σ(t, ω, γ0) = γ0.∑ n [G′ n (ω,γ0).sin(nωt)+G″ n (ω,γ0).cos(nωt)] (1)
[0253] In the formula
[0254] σ-stress response
[0255] t-time
[0256] ω-Frequency
[0257] γ0-strain amplitude
[0258] n - number of harmonics
[0259] G′ n -nth order elastic Fourier coefficient
[0260] G″ n -nth order viscosity Fourier coefficient
[0261] The nonlinear viscoelastic response was analyzed using large amplitude oscillatory shear (LAOS). Time sweep measurements were performed on an RPA 2000 rheometer from Alpha Technologies connected to a standard biconical die. During the measurement, the test chamber was sealed and a pressure of approximately 6 MPa was applied. The temperature of the LAOS test was 190°C, the angular frequency was 0.628 rad / s, and the strain was 1000%. To ensure that steady-state conditions were achieved, the nonlinear response was determined only after at least 20 measurement cycles were completed for each measurement. The large amplitude oscillatory shear nonlinear factor (LAOS_NLF) was defined as:
[0262]
[0263] In the formula
[0264] G′1-first order Fourier coefficient
[0265] G′3 - third-order Fourier coefficient
[0266] [1] JM Dealy, KF Wissbrun, Melt rheology and its effects on plastics processing: theory and applications; edited by Van Nostrand Reinhold, New York (1990)
[0267] [2] S. Filipe, Nonlinear rheology of polymer melts, AIP Conference Proceedings 1152, pp.168-174 (2009)
[0268] [3] M.Wilhelm, MacromoL.Mat.Eng.287, 83-105(2002)
[0269] [4] S. Filipe, K. Hofstadler, K. Klimke, A. Tran, Nonlinear rheological parameters for characterizing the molecular structure and properties of polyolefins, Proceedings of Annual European Rheology Conference, 135 (2010)
[0270] [5] S.Filipe, K.Klimke, A.T.Tran, J.Reussner, Research progress on nonlinear rheological parameters of novel molecular structures, Novel Trends in Rheology IV, Zlin, Check Republik (2011)
[0271] [6] K. Klimke, S. Filipe, A.T. Tran, Nonlinear rheological parameters for characterizing the molecular structure and properties of polyolefins, Proceedings of European Polymer Conference, Granada, Spain (2011)
[0272] s) Cross-fractionation chromatography
[0273] The chemical composition distribution of the polymer as well as the molecular weight distribution and the corresponding molecular weight averages (Mn, Mw and Mv) at a certain elution temperature (polymer crystallinity in solution) were determined by fully automated cross-fractionation chromatography (CFC) as described by Ortin A., Monrabal B., Sancho-Tello J., Macromol. Symp, 2007, 257, 13-28.
[0274] Cross-fractionation chromatography (TREF xSEC) was performed using a CFC instrument (PolymerChar, Valencia, Spain). The concentration was monitored using a quad-band IR5 infrared detector (PolymerChar, Valencia, Spain). The polymer was dissolved at 160°C for 150 minutes at a concentration of approximately 1 mg / ml.
[0275] To avoid injection of possible gels and polymers (such as PET and PA) that are not soluble in TCB at 160°C, the weighed samples were packed in stainless steel mesh with MW 0.077 / D 0.05 mm.
[0276] After the sample was completely dissolved, 0.5 ml of the sample was loaded into the TREF column and stabilized for a period of time at 110 ° C. At a constant cooling rate of 0.1 ° C / min, the polymer was crystallized and precipitated to a temperature of 30 ° C. The discontinuous elution process was performed using the following temperature steps: 35, 40, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 103, 106, 109, 112, 115, 117, 119, 121, 123, 125, 127, 130, 135 and 140).
[0277] In the second dimension, GPC analysis was performed using three PL Olexis columns and one Olexis Guard column from Agilent (Church Stretton, UK) as stationary phases. As eluent, 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol) was used, the temperature was 150 °C, and the flow rate was 1 mL / min. The columns were calibrated using universal calibration (according to ISO 16014-2:2003) using at least 15 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. PS molecular weights were converted to PP molecular weight equivalents using Mark Houwink constants.
[0278] KPS = 19x10 -3 mL / g, α PS =0.655
[0279] K PP =19x10 -3 mL / g, α PP =0.725
[0280] The calibration data were fitted using a third-order polynomial fitting method. The data were processed using the software provided by PolymerChar.
[0281] Calculation of relative fraction (in wt%) of iso-PP at a specific molecular weight and elution temperature range
[0282] In order to calculate the relative fraction of iso-PP (in wt%) at a specific molecular weight and elution temperature range, the first step is to calculate the amount of iso-PP (in wt%) in the CFC contour plot:
[0283] Iso-PP (wt%) = 100 -EPR fraction -PE fraction Formula (1)
[0284] Here, EPR refers to the fraction with a molar mass greater than the soluble fraction (SF) (obtained by CFC analysis, 35°C, in TCB) for a logM of 3.5
[0285]
[0286] Since the TREF curve is slightly dominated by the low MW portion, the molecular weight limit of the low MW limit depends on the elution temperature (T el ). The lower MW limit is determined by the following formula:
[0287] Lower MW limit (for PE fraction) = 0.0185*T el +3.1538
[0288] Considering the following, the PE fraction was calculated using the following method.
[0289]
[0290] In the formula, H ij is the corresponding elution temperature (T el )i and the two-dimensional differential distribution under logM value j is obtained by the corresponding data processing software.
[0291] The high crystalline PE fraction (HCF-PE) is defined as the portion of the PE fraction eluting from 90°C to 100°C.
[0292]
[0293] This fraction mainly contains PE homopolymer and PE copolymer, wherein the copolymer content is very low, less than about 3 SCB / 1000TC (L. Wild, TR Ryle, DC Knoblauch, IR Pay, J. Polym. Sci, Polym. Phys. 20, (1982), 441-455).
[0294] The low crystalline PE fraction (LCF-PE) is defined as the portion of the PE fraction eluting between 35°C and 89°C.
[0295]
[0296] This fraction contains mainly the copolymer fraction of HDPE and LLDPE obtained with ZN catalyst or LLDPE obtained with SS catalyst, but also contains LDPE, since these polymers have comparable SCB / 1000TC amounts and therefore co-elute.
[0297] Basic references:
[0298] Zhang, Macromol Symp. 282 (2009), 111-127.
[0299] W. Yau, D. Gillespie, Polymer 42 (2001) 8947-8958.
[0300] Monrabal, in "'Encyclopedia of Analytical Chemistry", RAMeyers, Ed., John Wiley & Sons Ltd., 2000.
[0301] Nakano, Y. Goto, J. Appl. Polym. Sci. (1981), 26, 4217.
[0302] W. Yau, Macromol. Symp. 2007, 257, 29-45.
[0303] Faldi, JBP Soares, Polymer 42(2001)3057-3066.
[0304] Ortin, B. Monrabal, J, Sancho-Tello, Macromol. Symp. 257 (2007), 13-28.
[0305] Li Pi Shan, D. Gillespie, L. Hazlitt, Ecorep 2005. Lyon.
[0306] Example
[0307] Post-consumer plastic waste is roughly sorted according to the properties and color of the polymers. Then, the white and colorless fractions are selected. The selected fractions are subjected to grinding, washing with various detergents in an aqueous solution, and then drying and screening. The pre-treated post-consumer plastic material is further sorted to reduce the colored part. In a further quality control step, the intermediates are subjected to cross-fractionation chromatography (automatic instrument combining TREF and CPC; commercially available from PolymerChar; see above for details). Intermediates whose low crystalline polyethylene fraction (LCF-PE) is not in the range of 2.8 to 4.2 wt% are discarded and returned to the new post-consumer waste. After extrusion into pellets, the pellets are aerated (aeration is used only for IE3; aeration conditions: air at 120°C, preheated substrate).
[0308] For Example IE4, the same process was used. However, after a rough sorting for polymer properties and color, the post-consumer plastic waste was screened for obvious very old ("ancient"), mainly colorless / natural plastic products, which can be identified by discoloration (such as obvious yellowing) and / or obvious scratches on the mainly colorless / natural plastic products. Strict criteria were followed for sorting these very old ("ancient"), mainly colorless / natural plastic products, i.e., in doubtful cases, the products in question were separated. The purpose of this was to exclude the incorporation of polybrominated diphenyl ethers, as many countries have banned the use of polybrominated diphenyl ethers for more than 10 years. In addition, the intermediates were screened for substances of very high concern. It was shown that partial warping was unnecessary.
[0309] All samples were subjected to CRYSTEX QC analysis.
[0310]
[0311]
[0312]
[0313]
[0314]
[0315] It can be seen that the recycled compositions of the present invention enrich the prior art. Compared with the original composition and the original visbroken composition, the recycled compositions of the present invention only show minor disadvantages in terms of impact. In addition, for IE2 and IE3, they have very good processability (reflected by high LAOS-NLF). For IE3 and IE4, they have unexpectedly good volatile organic compounds (VDA).
[0316] Comparative Example CE3 is a virgin random heterophasic PP copolymer. Therefore, the tensile modulus is relatively high due to the total amount of ethylene (reflected by the amounts of C2(CF) and C2(SF) as well as CF and SF). However, this is not a recycled material and the Charpy NIS is 7.1 kJ / m 2 The processability (reflected by LAOS-NLF) is relatively poor.
[0317] Comparative Example CE4 is the original random copolymer, which has been visbroken (the melt flow rate is adjusted to approximately the same value as IE4). The stiffness of CE4 is significantly lower than that of CE3, with a Charpy NIS of 7.6 kJ / m 2 The stiffness of the inventive example IE4 is slightly higher than that of CE3, and the best overall Charpy NIS is 8.5 kJ / m 2 Inventive Examples IE1 to 3 all have significantly higher stiffness while having only moderate Charpy NIS defects.
[0318] These examples were evaluated for surface defects on injection molded test articles. The highest commercial grades on the market (CE1 and CE2) were compared. The results are shown in Figure 1. Figure 1 shown.
[0319] CE1: Off-white polypropylene product, produced by Van Werven, density 920kg / m 3 , MFR (230℃ / 2.16kg) is 24g / 10min.
[0320] CE2: Regrind and regranulate material, supplied by Morssinkhof-Rymoplast under the name Density: 921kg / m 3, MFR (230℃ / 2.16kg) is 27g / 10min.
[0321] Figure 1 The results of the defect evaluation are shown. It can be seen that the mixed plastic polypropylene blend of the present invention produces the least number of defects and the defects are evenly distributed.
[0322] CE3 is a random multiphase copolymer without slip agent and anti-blocking additive. It has a random copolymer PP matrix and C3C2 rubber.
[0323] CE3 is produced in the Borstar polypropylene plant, which is equipped with a prepolymerization reactor, a slurry loop reactor, a first gas phase reactor and a second gas phase reactor. The loop reactor and the first gas phase reactor are used to produce the matrix, and the second gas phase reactor is used to produce the rubber phase.
[0324] The chemical composition of the reactants in each reactor is adjusted to achieve the desired polymer design.
[0325] CE4 is a random copolymer produced in the Borstar polypropylene plant, which is equipped with a prepolymerization reactor, a slurry loop reactor and a gas phase reactor.
[0326]
[0327] After polymerization, a visbreaking treatment was performed in a compounding step in a twin-screw extruder at a temperature of 200-230°C using an appropriate amount of Luperox 101 (2,5-dimethyl-2,5-di(tert-butylperoxy)hexane) to adjust the melt flow rate of the random copolymer CE4 to achieve a target MFR2 of 8.0 g / 10 min.
[0328] In the above compounding step, the following additives were added: 1000 ppm of Irganox B215 (a mixture of pentaerythritol-tetrakis(3-(3′,5′-di-tert-butyl-4-hydroxyphenyl)-propionate (CAS-no. 6683-19-8) and tris(2,4-di-tert-butylphenyl)phosphite (CAS-no. 31570-04-4), available from BASF SE, Germany) and 150 ppm of magnesium oxide (CAS no. 1309-48-4) as an acid scavenger.
[0329] The catalyst preparation method used in the CE3 and CE4 polymerization processes is as follows:
[0330] Chemicals used:
[0331] 20% butylethylmagnesium (Mg(Bu)(Et), BEM) solution in toluene, provided by Chemtura
[0332] 2-Ethylhexanol, supplied by Amphochem
[0333] 3-Butoxy-2-propanol (DOWANOL TM PnB) provided by Dow
[0334] Bis(2-ethylhexyl) citrate, provided by SynphaBase
[0335] TiCl4, supplied by Millenium Chemicals
[0336] Toluene, supplied by Aspokem
[0337] 1-254, provided by Evonik
[0338] Heptane, supplied by Chevron
[0339] Preparation of alkoxy magnesium compounds
[0340] The alkoxymagnesium solution was prepared by adding a mixture of 4.7 kg 2-ethylhexanol and 1.2 kg butoxypropanol to 11 kg 20 wt% butylethylmagnesium (Mg(Bu)(Et)) toluene solution in a 20 liter stainless steel reactor under stirring (70 rpm). During the addition, the temperature in the reactor was kept below 45°C. After the addition was complete, the reaction mixture was mixed (70 rpm) at 60°C for 30 minutes. After cooling to room temperature, 2.3 kg of the donor bis(2-ethylhexyl) citrate was added to the alkoxymagnesium solution, maintaining the temperature below 25°C. Mixing was continued for 15 minutes under stirring (70 rpm).
[0341] Preparation of solid catalyst components
[0342] In a 20-liter stainless steel reactor, 20.3 kg TiCl4 and 1.1 kg toluene were added. Mixing was performed at 350 rpm and the temperature was maintained at 0°C. 14.5 kg of the prepared alkoxy magnesium compound was added over 1.5 hours. 1.7 liters of After 1-254 and 7.5 kg of heptane were mixed at 0°C for 1 hour, the temperature of the formed emulsion was raised to 90°C within 1 hour. After 30 minutes, the mixing was stopped, the catalyst droplets solidified, and the formed catalyst particles were allowed to settle. After settling (1 hour), the supernatant was sucked off with a siphon. The catalyst particles were then washed with 45 kg of toluene at 90°C for 20 minutes, followed by two heptane washes (30 kg, 15 minutes). The temperature was lowered to 50°C during the first heptane wash and to room temperature during the second wash.
[0343] In addition, in the polymerization process of random copolymers (compare CE3, CE4), the phthalate-free Ziegler-Natta catalyst described in the example section as a "reference catalyst" in WO 2020 / 064673A1 can also be used.
[0344] The catalyst thus obtained was used together with triethylaluminium (TEAL) (as cocatalyst) and dicyclopentyldimethoxysilane (D-Donor) (as donor).
[0345] The IE4 substances of very high concern (SVHC) were further evaluated. The results are shown in Table 2 below.
[0346] Table 2: Evaluation of IE4 substances of high concern:
[0347]
[0348] RoHS - Restriction of Hazardous Substances in Electrical and Electronic Equipment
[0349] RL - Lower detection limit (if ≥RL, the test data is displayed. RL is not a specified limit)
[0350] Method for SVHC (according to REACH Regulation 1907 / 2006 / EU)
[0351] The entire analysis process is completed at SGS.
[0352] The methods in the SGS laboratory include CTS-HL-114-1 and CTS-HL-234-5, and the analytical methods include ICP-OES, UV-VIS, GC-MS, HPLC-DAD / MS and colorimetry.
[0353] Determination of Cadmium by ICP-OES in accordance with IEC 62321-5:2013-6
[0354] Determination of lead by ICP-OES in accordance with IEC 62321-5:2013-6
[0355] Determination of mercury by CV-AAS in accordance with IEC 62321-4:2013-6
[0356] Determination of Chromium by ICP-OES in accordance with IEC 62321-5:2013-6
[0357] Determination of chromium (VI), in accordance with IEC62321-> non-metallic samples;
[0358] Determination by ion chromatography, in accordance with IEC 62321-7-2:2017-03;
[0359] Note: The concentration of chromium (VI) in the preservative will vary with storage time and conditions.
[0360] Determination of PBB / PBDE (flame retardants) by gas chromatography / mass spectrometry in accordance with IEC 62321-6:2015-6
[0361] Note: According to IEC standards, PBB / PBDE is only tested on polymers.
[0362] Softeners DEHP, DBP, BBP, DIBP and extended list stipulated by REACH (IEC 62321-8:2017, GC-MS)
[0363] Determination of phthalates by gas chromatography / mass spectrometry after extraction with THF in accordance with IEC 62321-8:2017-3; method not yet compliant
[0364] Note: According to IEC standards, phthalates are only tested on polymers.
[0365] CE3 is a bimodal virgin random polypropylene, which was evaluated for comparative purposes. It can be seen that replacing the virgin random polypropylene with the blend of the present invention produces surprising results in terms of impact.
[0366] As a further application example, injection moulded barrels were produced using standard process settings. The results showed that the surface quality was just as good as that of similar virgin materials. The thickness distribution and mechanical properties were also excellent.
Claims
1. Mixed plastic polypropylene blend, with (i) the crystalline fraction (CF) content determined by CRYSTEX QC analysis is 86.0-94.0 wt %, as well as (ii) 6.0-14.0 wt% soluble fraction (SF) content as determined by CRYSTEX QC analysis, in (iii) the propylene content (C3(CF)) of the crystalline fraction (CF) is 95.0-99.0 wt %, and the propylene content (C3(CF)) is determined by quantitative 13 C-NMR spectra were calibrated with FT-IR spectra, where (iv) the ethylene content (C2(CF)) of the crystalline fraction (CF) is 1.0-5.0 wt %, and the ethylene content (C2(CF)) is determined by quantitative 13 FT-IR spectrometry with calibration of C-NMR spectra; (v) the soluble fraction (SF) has an intrinsic viscosity (iV(SF)) of 1.10 to less than 1.50 dl / g; in (vi) the mixed plastic polypropylene blend has an inorganic residue of 0.05 to 3.0 wt. % relative to the mixed plastic polypropylene blend, the inorganic residue being determined by calcination analysis (TGA) according to DIN ISO 1172:1996; (vii) the mixed plastic polypropylene blend does not contain benzene above the HS GC-MS 80°C / 2h detection limit; (viii) the mixed plastic polypropylene blend has a CIELAB color space (L*a*b*), wherein: - L* is 72.0 to 97.0; -a* is -5.0 to 0.0; - b* is 0.0 to less than 22.0; and (ix) the mixed plastic polypropylene blend has a large amplitude oscillatory shear-nonlinear factor (LAOS-NLF) greater than 2.3 measured at 190° C. and a strain of 1000%, wherein: In the formula G1 ’ is the first-order Fourier coefficient G3 ’ is the third-order Fourier coefficient, Wherein, the mixed plastic polypropylene blend is a recycled material, The mixed plastic polypropylene blend is obtained by the following steps: a) Provide post-consumer plastic waste; b) Sorting of commodities made of polystyrene, polyamide, polyethylene, metal, paper, wood and other non-polypropylene materials to provide post-consumer plastic materials; c) Sorting of colored commodities and providing post-consumer plastic materials; d) grinding the selected predominantly white or colorless post-consumer plastic material, washing it in an aqueous solution with various detergents, and then drying, air-sieving and screening it; e) further sorting the pretreated post-consumer plastic material to remove non-polyolefins and colored components to obtain an intermediate; f) a quality control step, wherein the intermediate obtained in step e) is subjected to cross fractionation chromatography, i.e. CFC, to determine the low crystalline polyethylene fraction (LCF-PE) in CFC and to check again whether the amount is within the range of 2.0 to 4.0 wt%; g) discarding the intermediate having a low crystalline polyethylene fraction not in the range of 2.8 to 4.2 wt %; h) extruding the material.
2. The mixed plastic polypropylene blend as claimed in claim 1, wherein: The melt flow rate of the mixed plastic polypropylene blend measured under the conditions of a load of 2.16 kg and 230° C. according to ISO1133 is 2.0-100 g / 10 min.
3. A mixed plastic polypropylene blend as claimed in any one of the preceding claims, wherein: The mixed plastic polypropylene blend contains one or more of the following substances: a) Polystyrene; b) polyamide-6; c) Limonene, determined by solid phase microextraction (HS-SPME-GC-MS); d) Fatty acids were determined by solid phase microextraction (HS-SPME-GC-MS).
4. The mixed plastic polypropylene blend according to claim 1 or 2, wherein: The ethylene content (C2(SF)) of the soluble fraction (SF) obtained by CRYSTEX QC analysis is 12.0-32.0 wt %. The ethylene content (C2(SF)) is determined by quantitative 13 C-NMR spectra were calibrated with FT-IR spectra.
5. The mixed plastic polypropylene blend according to claim 1 or 2, wherein: The mixed plastic polypropylene blend has an odor grade of 4 or less expressed as VDA270-B3.
6. The mixed plastic polypropylene blend according to claim 1 or 2, wherein: The large amplitude oscillatory shear-nonlinear factor (LAOS-NLF) of the mixed plastic polypropylene blend measured at 190° C. and a strain of 1000% is greater than 2.7, wherein In the formula G1 ’ is the first-order Fourier coefficient G3 ’ are the third-order Fourier coefficients.
7. The mixed plastic polypropylene blend according to claim 1 or 2, wherein: The mixed plastic polypropylene blend has a tensile modulus of at least 1200 MPa measured according to ISO 527-2 at a crosshead speed of 1 mm / min and 23° C., the tensile modulus being determined using dog-bone shaped, 4 mm thick injection molded specimens as described in EN ISO 1873-2.
8. The mixed plastic polypropylene blend according to claim 1 or 2, wherein: The mixed plastic polypropylene blend has a non-instrumented Charpy notched impact strength (NIS) (1eA) of at least 8.0 kJ / m at +23°C measured according to ISO 179-1eA using 80×10×4 mm injection molded specimens prepared as described in EN ISO 1873-2. 2 , wherein, further, the ethylene content (C2(SF)) of the soluble fraction (SF) obtained by CRYSTEX QC analysis is 12.0-20.0 wt%, and the ethylene content (C2(SF)) is determined by quantitative 13 C-NMR spectroscopy calibrated FT-IR spectroscopy, and further, the mixed plastic polypropylene blend has a CIELAB color space (L*a*b), wherein - L* is 72.0 to 97.0; -a* is -5.0 to 0.0; -b* is 0.0 to less than 22.0, And further, the crystalline fraction (CF) content determined according to CRYSTEX QC analysis is 91.0-94.0 wt %, and the soluble fraction (SF) content determined according to CRYSTEX QC analysis is 6.0-9.0 wt %.
9. The mixed plastic polypropylene blend according to claim 1 or 2, wherein: The mixed plastic polypropylene blend is in the form of pellets.
10. The mixed plastic polypropylene blend according to claim 1 or 2, wherein: The mixed plastic polypropylene blend is visbroken by peroxide.
11. A molded article made from the mixed plastic polypropylene blend of claim 1 or 2.
12. Blend comprising the mixed plastic polypropylene blend according to claim 1 or 2 and at least one virgin polyolefin.
13. A blend comprising the mixed plastic polypropylene mixture according to claim 1 or 2 and at least one virgin polyolefin, wherein: The at least one pristine polyolefin is a heterophasic polypropylene.
14. Use of the mixed plastic polypropylene blend as claimed in claim 1 or 2 in the packaging and / or medical fields.
Citation Information
Patent Citations
Electro-optical transducer module
CA1309484C
Process for removing volatiles from post-consumer recycled polyolefin chips
US5767230A
Method for producing polyolefin recyclates
WO2018046578A1
Process for producing a heterophasic propylene copolymer having a high xylene cold soluble fraction (XCS)
WO2020064673A1
Multimodal polyethylene composition with high pressure resistance
CN105849177A
